2013
DOI: 10.4103/0971-4065.107188
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological aspects of peritonitis in patients on continuous ambulatory peritoneal dialysis

Abstract: The objective of the study was to identify the microbiological spectrum and drug-sensitivity pattern of peritonitis in patients on continuous ambulatory peritoneal dialysis. This was a prospective study done over a period of a year-and-a-half at a tertiary-care hospital in a hilly state of India. The effluent dialysate bags from 36 consecutive patients with peritonitis were studied. One hunderd ml dialysate fluid was processed under aseptic conditions by lysis centrifugation method. Microscopy and culture was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Standard antituberculous chemotherapy is highly effective. Therefore, it is prudent to start empirical treatment with antituberculous chemotherapy in CAPD patients with peritonitits that is refractory to broad-spectrum antibiotics while awaiting the results of the mycobacterial cultures to improve the outcome and preserve peritoneal membrane integrity (30).…”
Section: Discussionmentioning
confidence: 99%
“…Standard antituberculous chemotherapy is highly effective. Therefore, it is prudent to start empirical treatment with antituberculous chemotherapy in CAPD patients with peritonitits that is refractory to broad-spectrum antibiotics while awaiting the results of the mycobacterial cultures to improve the outcome and preserve peritoneal membrane integrity (30).…”
Section: Discussionmentioning
confidence: 99%
“…About one-fifth of the cases of peritonitis were caused by CoNS in this study (Vikrant et al, 2013). Also, there are studies which have reported that the majority of CAPD peritonitis was caused by CoNS which may primarily be due to touch contamination or due to the formation of a biofilm.…”
Section: Resultsmentioning
confidence: 52%
“…Similar findings were observed in other studies. 3,14 Fungi are uncommonly implicated, being responsible for only 2-16% of all peritonitis episodes associated with CAPD. 15 Fungal peritonitis, if not detected early and treated appropriately, is associated with increased morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%